ANALISIS RANTAI PASOK (SUPPLY CHAIN) GARAM RAKYAT DI KABUPATEN PIDIE, ACEH - Athaillah, Teuku; Nugroho, Yoga (Universitas Medan Area, 2019)
The purpose of this research is to analyze the product, financial, and information flow in the local salt supply chain in Pidie Regency, Aceh. The sampling technique used is non-probability sampling, precisely the snowball sampling technique. Product flow, financial flow, and information flow were three elements that investigated. The analysis based on the SCOR (Supply Chain Operation Reference) method to see supply chain performance by studying at the Plan, Source, Make, and Deliver process. The results showed two types of supply chains, depends on whether farmers have an agreement with the collecting agent or not. For farmers who had a deal with the collecting agent, The salts are sold to the collecting agent and then forwarded to the selling agent. The selling agent passes it on to the wholesale seller, who then distributed to retailers and consumers. The flow of finance goes from the opposite direction, except when purchasing raw materials for firewood, the collecting agent pays it first to the farmers. To farmers who did not have agreements with collecting agents, the salt directly sold to retail stores or consumers. Financial flows run in the opposite direction for both types of supply chains, and information flow goes both ways. The main obstacle in the salt supply chain is the lack of information between salt producer and consumers expectations. Moreover, it is often difficult for large customers to believe that the quality of farmers' salt will be consistent.Kata Kunci : supply chain; local salt; SCOR;.